EVALUASI GENANGAN PADA LAPANGAN SEPAK BOLA DI STADION SULTAN AGUNG KABUPATEN BANTUL - Renanda Anggriaswati; Yeri Sutopo (DAS Institute, 2022)
Sultan Agung Stadium is one of Indonesia's premier league stadiums and international standards with a subsurface drainage system. Subsurface drainage is considered to be very efficient compared to surface drainage. However, during heavy rains, there are still some puddles on the surface of the football field. The presence of puddles is a massive problem in a football match because it can block the flow of the ball. The purpose of this study was to evaluate the drainage system of the Sultan Agung Stadium football field in terms of the diameter, depth, and distance between the subdrain pipes. The data analyzed include soil, rainfall, and drainage dimension data. Soil data was used to analyze the infiltration test, soil porosity, and permeability. Rainfall data is used for hydrological analysis by determining the design rainfall at 2, 5, and 10-year return periods, and drainage dimension data is used for hydraulics analysis by determining the pipe capacity and drain layer. Based on the results of this study, a pipe with a diameter of 6 inches with a distance of 5 m cannot overcome inundation during the 10-year return period. Variations in depth and distance between drainage pipes are known to have an effect on inundation that occurs in the field. By reducing the distance to 4m, the inundation that occurs can be resolved